TEKNIK PENANAMAN JAJAR LEGOWO UNTUK PENINGKATAN PRODUKTIVITAS PADI SAWAH DI JAWA TENGAH - Octavia Rizky Prasetyo; Kadir Kadir (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
This research is aimed to analyse the distribution of a cultivation technique of wetland paddy so-called “Jajar Legowo” in Central Java Province as well as its impact on paddy productivity. We made use of the Results of the 2017 Cost Structure of Food Crops Cultivation Survey carried out by Statistics Indonesia (BPS). A spatial analysis and an estimation of Ordinary Least Square (OLS) regression model was used to achieve aims. Our results pointed out that the wetland paddy households implementing the technique only made up about 32.05 per cent of the total number of wetland paddy households in Central Java. They were concentrated in some municipalities, i.e., Prubalingga, Banjarnegara, Grobogan, Kudus, Demak, Temanggung and Kendal. Meanwhile, the OLS estimations showed that the technique has a significant impact in boosting productivity up to 16 per cent compared to other cultivation techniques. Therefore, it could be a key measure in increasing rice production in Central Java. Moreover, our findings also pointed out that other measures such as enhancing the capacity of farmers, the use of high-quality seed and mechanisation and improving the access on financial resources also have a pivotal role in improving the productivity of paddy in the province.